2009
DOI: 10.1002/pssb.200844272
|View full text |Cite
|
Sign up to set email alerts
|

Non‐DMS related ferromagnetism in transition metal doped zinc oxide

Abstract: We review pitfalls in recent efforts to make a conventional semiconductor, namely ZnO, ferromagnetic by means of doping with transition metal ions. Since the solubility of those elements is rather low, formation of secondary phases and the creation of defects upon low temperature processing can lead to unwanted magnetic effects. Among others, ion implantation is a method of doping, which is highly suited for the investigation of those effects. By focussing mainly on Fe, Co or Ni implanted ZnO single crystals w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 103 publications
1
31
0
Order By: Relevance
“…Many avenues have been followed to accomplish these objectives, and several mechanisms, such as defects [4] or carrier mediation [5], have been proposed to explain the occasional observations of long-range magnetic order, often based on large hole concentrations [6] or oxygen vacancies in doped ZnO [7]. For ZnCo 2 O 4 , on the other hand, which is widely known as anode material in lithium batteries [8] and as crystalline, or amorphous p-type gate in junction field-effect transistors [9], it has also been reported that the provided oxygen partial pressure during growth can change the conduction type and even the magnetic properties from paramagnetic to ferromagnetic [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many avenues have been followed to accomplish these objectives, and several mechanisms, such as defects [4] or carrier mediation [5], have been proposed to explain the occasional observations of long-range magnetic order, often based on large hole concentrations [6] or oxygen vacancies in doped ZnO [7]. For ZnCo 2 O 4 , on the other hand, which is widely known as anode material in lithium batteries [8] and as crystalline, or amorphous p-type gate in junction field-effect transistors [9], it has also been reported that the provided oxygen partial pressure during growth can change the conduction type and even the magnetic properties from paramagnetic to ferromagnetic [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the necessary use of thick substrates for growing those oxides makes the interpretation of magnetometry data complicated, i.e. one has to exclude any ferromagnetic contamination in their substrates 28,29 . For carbon-based material,…”
Section: Introductionmentioning
confidence: 99%
“…There is much evidence to suggest that ferromagnetism in transition-metal doped ZnO is unambiguously correlated with structural defects, which depend on the substrate temperature and oxygen pressure used during film deposition [2], [3]; the charge carriers are byproducts of these defects. Ney et al [4] have demonstrated that highly perfect Co-doped epitaxial films, for example, are purely paramagnetic, with cobalt occupying zinc sites and no sign of anything other than weak antiferromagnetic Co-O-Co nearest-neighbour superexchange.…”
Section: Introductionmentioning
confidence: 99%